Changes in Tax System, Company Size, Income, Liquidity and NDTS Influence to Indonesian Manufacturing Company's Capital Structure (2006-2011) - admin, SHINTA PERMATA PUTRI B12112001 (Jurnal Manajemen Update, 2016)
ABSTRAK There are several factors that influence Companyâ€™s financing choice. Several of the most well know factor are income, liquidity, non-debt tax shield, and size. Tax is a very important factor in capital structure decision. Yet, the study that observe the relation between at tax rate and capital structure is still very limited. The opportunity to observe tax rate influence to capital structure in Indonesian Firm came at year 2008. Act no 36 year 2008, written in 5th tax reform in Indonesia change progressive tax rate to flat tax rate. This paper study the structure of manufacturing companies listed on BEI (2006-2010) and the factor that influence the capital structure. In total, there are 288 data gathered from 48 companies. The data was processed using eviews7. The result showed that the change in tax system managed to lower manufacturing company tendency to use debt financing. There are no significant relation between profitability (ROE) and NDTS toward debt percentage. Size and liquidity have negative relationship to leverage ratio Â  Keyword: Tax reform, capital structure, manufacturing industry